Observations of iodine oxide in the Indian Ocean marine boundary layer: A transect from the tropics to the high latitudes. (January 2019) - Mahajan, Anoop S.; Tinel, Liselotte; Hulswar, Shrivardhan; Cuevas, Carlos A.; Wang, Shanshan; Ghude, Sachin; Naik, Ravidas K.; Mishra, Rajani K.; Sabu, P.; Sarkar, Amit; Anilkumar, N.; Saiz Lopez, Alfonso
Abstract: Observations of iodine oxide (IO) were made in the Indian Ocean and the Southern Ocean marine boundary layer (MBL) during the 8th Indian Southern Ocean Expedition. IO was observed almost ubiquitously in the open ocean with larger mixing ratios south of the Polar Front (PF). Contrary to previous reports, IO was not positively correlated to sea surface temperature (SST)/salinity, or negatively to chlorophyll a . Over the whole expedition, SST showed a weak negative correlation with respect to IO while chl a was positively correlated. North of the PF, chl a showed a strong positive correlation with IO. The computed HOI and I2 fluxes do not show any significant correlation with atmospheric IO. Simulations with the global CAM-Chem model show a reasonably good agreement with observations north of the PF but the model fails to reproduce the elevated IO south of the PF indicating that the current emission parametrizations are not sufficient to explain iodine chemistry in the Southern Indian Ocean. Highlights: Latitudinal transect for atmospheric iodine species in Indian and Southern Ocean. Model discrepancy suggests iodine chemistry is poorly understood in the SO. Inorganic HOI and I2 fluxes are poor proxies for predicting IO over the SO. Chlorophyll a correlates better indicating a missing biogenic source in that region.